Dynamic-weighted joint beamforming design for communication and sensing in fluid antenna-assisted ISAC system - LI Fei; ZHANG Jie; LI Ting; SONG Yunchao (Tongxin xuebao, 2025)
To address the challenges in achieving dynamic communication-sensing trade-offs and the high complexity of conventional optimization methods in existing fluid antenna (FA)-assisted integrated sensing and communication (ISAC) systems, a weighted joint optimization scheme for FA-assisted ISAC beamforming was proposed. Firstly, a weighted sum maximization model of communication sum-rate and sensing beam pattern gain was established. The communication rate maximization problem was transformed into a weighted minimum mean square error (WMMSE) minimization formulation, with joint optimization of the beamforming matrix and transceiver antenna positions under transmit power constraints. Then, for the non-convex optimization problem involving beamforming matrices and FA positions, an alternating optimization algorithm was employed to decompose it into beamforming and position optimization subproblems. Convex relaxations were constructed by integrating Taylor expansion and the majorization-minimization (MM) algorithm, and closed-form solutions were derived. The simulation results demonstrate that the proposed scheme significantly outperforms traditional ISAC systems in both total communication rate and beam pattern gain. Furthermore, flexible trade-offs between communication and sensing performance are achieved by adjusting weight parameters.